2021
DOI: 10.3389/fcell.2021.772223
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection and Axonal Regeneration Induced by Bone Marrow Mesenchymal Stromal Cells Depend on the Type of Transplant

Abstract: Mesenchymal stromal cell (MSC) therapy to treat neurodegenerative diseases has not been as successful as expected in some preclinical studies. Because preclinical research is so diverse, it is difficult to know whether the therapeutic outcome is due to the cell type, the type of transplant or the model of disease. Our aim here was to analyze the effect of the type of transplant on neuroprotection and axonal regeneration, so we tested MSCs from the same niche in the same model of neurodegeneration in the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 78 publications
2
19
0
Order By: Relevance
“…The neuroprotective role of IL-6 goes through modulation of excitability and function by regulating voltage-gated and receptor operated channels, which in turn are critical for neuronal electrical functionality (reviewed in [ 55 57 ]). Here, levels of IL-6 three times higher than basal conditions did not cause RGC death, and thus, it is tempting to speculate that in this context IL-6 is not detrimental but beneficial, which concords with the maintenance of functionality seen here and the neuroprotective and neuroregenerative properties of syngeneic BM-MSCs [ 18 ].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The neuroprotective role of IL-6 goes through modulation of excitability and function by regulating voltage-gated and receptor operated channels, which in turn are critical for neuronal electrical functionality (reviewed in [ 55 57 ]). Here, levels of IL-6 three times higher than basal conditions did not cause RGC death, and thus, it is tempting to speculate that in this context IL-6 is not detrimental but beneficial, which concords with the maintenance of functionality seen here and the neuroprotective and neuroregenerative properties of syngeneic BM-MSCs [ 18 ].…”
Section: Discussionmentioning
confidence: 93%
“…Previously, we showed that the syngeneic intravitreal transplant of BM-MSCs was neuroprotective and promoted axonal regeneration of axotomized RGCs, while allogeneic transplant did not differ from un-transplanted retinas. Xenogeneic transplant, however, impaired retinal functionality further than axotomy alone [ 18 ]. Those data tie beautifully with data presented here, where we show that in the healthy retina, the syngeneic transplants neither alter retinal function nor cause glial activation, while allo- and xenotransplants do, being the latter the most damaging transplant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings contrast with other reports that MSCs injected intravitreally did not integrate into the rat retina (Hill et al, 2009 ), and even after 18 weeks post-injection, the majority of BM-MSCs remained in the vitreous body (Mesentier-Louro et al, 2014 ). Importantly, a recent study indicated that care with the type of transplantation of cells (syngeneic, allogeneic, or xenogeneic) may impact the results, since MSCs from different donor species can exert different effects (Norte-Munoz et al, 2021 ).…”
Section: Msc Therapy In Neurological Diseasesmentioning
confidence: 99%